A novel in situ and graded sampling system for seawater microplastics - Lv, Hongmin; Gao, Nan; Sun, Zhongliang; Kong, Xiangfeng (Tecnología y ciencias del agua, 2022)
The net trawling method requires complicated operations, during which samples are susceptible to contamination in an open environment. In this context, a novel in situ and graded sampling system for seawater microplastics was developed. This system integrates the collection, separation, and enrichment procedures and features alternate air-water elution and three-layer graded collection (membrane mesh sizes of 300, 100, and 50 Î¼m). Its advantages are ease of operation, reduced operation time, seawater recycling, and forming a closed space to avoid sample contamination. Moreover, it is capable of measuring the filtered seawater volume accurately. An in-shore experiment was carried out to collect microplastic samples with the new system. These samples were analyzed and identified by micro-Raman spectroscopy. Microplastics with different types (PE, PET, PA, PEVA, PS, and PVS); colors (translucent, white, blue, and yellowish), and shapes (foam, fragment, fiber, and granule) were found on the 100 and 50 Î¼m filter membranes but not on the 300 Î¼m filter membrane. The results indicate that the new sampling system effectively collects microplastics usually omitted by trawling nets and can be used as a supplement to trawling nets.